2003
DOI: 10.1002/bmc.263
|View full text |Cite
|
Sign up to set email alerts
|

Versican undergoes specific alterations in the fine molecular structure and organization in human aneurysmal abdominal aortas

Abstract: Versican is the major matrix proteoglycan in aortic wall and participates in various biological functions of the tissue. In the present study the molecular characteristics of versican isolated from normal human aorta as well as those of versican expressed in aneurysmal aortic tissue were examined. Versican was isolated by combined anion-exchange and gel permeation chromatography and was further characterized by high-performance liquid chromatography, polyacrylamide gel electrophoresis and immunoblotting. In bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Indeed, according to previous investigations, this metalloprotease is much more efficient in degrading PGs than other MMPs, such as MMP-1 and MMP-9. Therefore, matrilysin and stromelysin-1 probably share the ability to bind to the sulfated residues of the mucoid substance and to degrade the core of the native PGs of the aortic wall, thereby profoundly modifying the glycosaminoglycan environment of the aortic SMCs [37]. Similar data have already been reported in osteoarthritis, where matrilysin was associated with modified glycosaminoglycans of pathological cartilage [38], and in atherosclerosis in association with versican [34].…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Indeed, according to previous investigations, this metalloprotease is much more efficient in degrading PGs than other MMPs, such as MMP-1 and MMP-9. Therefore, matrilysin and stromelysin-1 probably share the ability to bind to the sulfated residues of the mucoid substance and to degrade the core of the native PGs of the aortic wall, thereby profoundly modifying the glycosaminoglycan environment of the aortic SMCs [37]. Similar data have already been reported in osteoarthritis, where matrilysin was associated with modified glycosaminoglycans of pathological cartilage [38], and in atherosclerosis in association with versican [34].…”
Section: Discussionmentioning
confidence: 51%
“…They can also activate other proteases and cleave PGs [35]. Versican is one of the PGs that can be degraded by MMP-7 [36,37]. Indeed, according to previous investigations, this metalloprotease is much more efficient in degrading PGs than other MMPs, such as MMP-1 and MMP-9.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The concentration of versican in the arterial wall was 89% lower in patients with aneurysms (Theocharis et al, 2001). Further research found a significant increase in the versican degradation fragment in the vascular wall in aortic aneurysm tissues (Theocharis et al, 2003). These studies suggest that versican degradation may be associated with the progression of aortic dissection or aneurysm.…”
Section: Discussionmentioning
confidence: 77%
“…For example, in addition to the full-length core protein (at >350 kDa), we observed strongly reactive bands migrating at 160 and 300 kDa in Western blots of deglycosylated extracts of normal human aorta (Sandy et al 2001). Such lower molecular weight species were also observed in conditioned medium of cultured human smooth muscle cells (SMCs) (Sandy et al 2001) and in human atherosclerotic plaques (Formato et al 2003) and aneurysms (Theocharis et al 2003). Moreover, distinct fragments of versican were detected in normal bovine and mouse aortas (Figure 2).…”
Section: The Nature Of Versican In the Blood Vesselmentioning
confidence: 77%